Involvement of new oxidative stress markers in chronic spontaneous urticaria - Nettis, Eustachio; Distaso, Maria; Saitta, Salvatore; Casciaro, Marco; Cristani, Mariateresa; Saija, Antonina; Vacca, Angelo; Gangemi, Sebastiano; Minciullo, Paola L. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Oxidative stress is a result of an imbalance between endogenous production of free reactive oxygen species and reduced effectiveness of antioxidant defence mechanisms. Advanced glycation end products (AGEs) and advanced oxidation protein products (AOPPs) are compounds formed by transformation of macromolecules, including proteins which can serve as markers of oxidative stress and inflammation in several diseases. Aim : To investigate the role of AGEs and AOPPs as new markers of oxidative stress and inflammation in patients with chronic spontaneous urticaria (CSU). Material and methods : Advanced glycation end products and AOPP levels were determined in the sera of 85 patients with CSU and 64 healthy controls, using spectrofluorimetry and spectrophotometry, respectively. Results : Advanced oxidation protein products levels in patients were statistically higher than those in controls. These levels were not affected by the presence of positive autologous serum test results or autologous plasma test results. No statistically significant differences were found between AGE levels in patients and controls. Conclusions : Formation of AGEs and AOPPs may be accelerated in immunological and allergic disorders. Depending on the sites evaluated, the presence or absence of oxidative stress in chronic urticaria is controversial. To our knowledge, this is the first study showing the possible involvement of AOPPs in CSU. The different behaviour observed for these two biomarkers is very likely due to the activation of specific related biochemical pathways associated with the condition under study.